Moral e religião em Kant: um estudo sob a ótica deontológica do pensamento kantiano - Prestes, Carlos Domingos (My University, 2020)
The present dissertation studies the Kantian moral philosophy and the thought about the religion in Kant from the perspective of a unity between them based on moral principles. This dissertative study consults the main Kantian works on these subjects, with emphasis on the books Grounding of the metaphysics of customs and Religion within the limits of simple reason. The dissertation relates the deontological ethics of the book of Grounding with Christian morality, according to Kant's rational interpretation of Christianity presented in the book of Religion. She also points to Kant'stransition from moral to religion in the concept of Highest Good and in the essay On the Failure of All Philosophical Judgments in Theodicy. It also shows the link between the moral philosophy of the Grounding book and the philosophy of religion as it is exposed book of Religion, which points to morality, good conduct as the essence of religion in rational terms, so that right behavior cannot be left aside in the reflection on the religious phenomenon, particularly Christian. The dominant method employedinterpretative is the analytical-interpretative. The hermeneutic method is partially used in the second part of the dissertation. The research is bibliographic. From the perspective of duty, it appears that the individual, particularly the religious, cannot ignore the idea of good conduct in the name of inclinations in his interpersonal relationships, and that the motivation of actions is something important in the ethical sphere, which it no can be negotiated in the name of calculating thinking.
A presente dissertação estuda a filosofia moral kantiana e o pensamento acerca da religião em Kant sob a perspectiva de uma unidade entre as mesmas fundamentada em princípios morais. Esse estudo dissertativo consulta as principais obras kantianas sobre esses assuntos, com ênfase nos livros Fundamentação da metafísica dos costumes e A religião nos limites da simples razão. A dissertação relaciona a ética deontológica do livro da Fundamentação com a moral cristã, conforme a interpretação racional do Cristianismo de Kant apresentada no livro da Religião. Ela também aponta a transição da moral à religião em Kant no conceito de Sumo Bem e no ensaio Sobre o insucesso de todos os julgamentos filosóficos na teodiceia. Ela ainda mostra o vínculo entre a filosofia moral do livro da Fundamentação com a filosofia da religião tal como é exposta no livro da Religião, a qual aponta a moralidade, a boa conduta como a essência da religião em termos racionais, de modo que o comportamento correto não possa ser deixada de lado na reflexão sobre o fenômeno religioso, particularmente cristão. O método empregado dominante é o analítico-interpretativo. Usa-se parcialmente o método hermenêutico na segunda parte da dissertação. A pesquisa é bibliográfica. Sob a ótica do dever se constata que o indivíduo, particularmente o religioso, não pode deixar de lado a ideia da boa conduta em nome das inclinações nas suas relações interpessoais, e que a motivação das ações é algo importante na esfera ética, a qual não pode ser negociada em nome de um pensamento calculista.
Keywords: Kant, Immanuel, 1724-1804 - Filosofia; Ética; Razão; Religião; Ethic; Reason; Religion